The use of obstetric ultrasound in the antenatal diagnosis of craniosynostosis: We need to do better. Issue 3 (30th May 2016) - Constantine, Sarah; David, David; Anderson, Peter
Abstract: Introduction: The cranial sutures allow for growth of the developing brain in both the pre‐ and post‐natal period but also play a crucial role in vaginal delivery. Birth problems are commonly reported by the mothers of children with craniosynostosis and, in particular, sagittal synostosis. Methods: Patients presenting with all forms of craniosynostosis were identified through a search of computer records, and the antenatal imaging was obtained and examined. The fetal cranial measurements including biparietal diameter, occipitofrontal diameter and head circumference were recorded, and the cephalic index (CI) was calculated for each affected fetus. A birth history was also recorded. Results: Scans in both the second and third trimesters were available for 28 fetuses who had sagittal synostosis. Eight fetuses (29%) had a significant reduction in CI (>3) between the morphology and growth scans. There was an increase in the number of emergency caesarean deliveries in women whose fetuses had sagittal synostosis when compared with the general population (22% vs. 17%). Conclusion: The calculation of CI can be performed routinely at antenatal scanning. A value outside the normal range or a change in CI during the pregnancy should prompt detailed scanning of the fetal skull and cranial sutures. This will assist obstetricians with delivery planning.